PENDAFTARAN HAK TANGGUNGAN ELEKTRONIK PADA BADAN PERTANAHAN NASIONAL KOTA DEPOK - Evangelista Ester Kinasih Dewanti SIbarani (2021)
The change of Conventional Mortgage Rights to Electronic Mortgage Rights (HT-el) is one of the transformations held by the Ministry of Agrarian Spatial Planning / National Land Agency (ATR / BPN). This is in line with the issuance of Permen ATR / BPN No. 5/2020 concerning Electronically Integrated Mortgage Services as a substitute for Permen ATR / BPN No. 9 of 2019. This study will discuss the procedures for implementing HT-el service registration based on Permen ATR / BPN No. 5 of 2020 and evaluation of services at the Depok City Land Office. The research method used in this article is juridical empirical. This study concludes that the implementation procedure for HT-el registration starts with PPAT inputting documents and other files, then financial services submits HT-el registration, finally the Land Office checks and processes the registration for registration and issues a certificate of mortgage. From this process flow, the Land Office is still experiencing technical problems in terms of equipment, networks and human resources, as well as filing inputted by PPAT & Financial Services. Keywords: Electronic Mortgage, Land Office, Evaluation.